A Room‐Temperature Ferroelectric Ferromagnet in a 1D Tetrahedral Chain Network. Issue 24 (29th April 2019) - Kang, Kyeong Tae; Roh, Chang Jae; Lim, Jinyoung; Min, Taewon; Lee, Jun Han; Lee, Kyoungjun; Lee, Tae Yoon; Kang, Seunghun; Seol, Daehee; Kim, Jiwoong; Ohta, Hiromichi; Khare, Amit; et al.
Abstract: Ferroelectricity occurs in crystals with broken spatial inversion symmetry. In conventional perovskite oxides, concerted ionic displacements within a 3D network of transition‐metal–oxygen polyhedra ( M O x ) manifest spontaneous polarization. Meanwhile, some 2D networks of M O x foster geometric ferroelectricity with magnetism, owing to the distortion of the polyhedra. Because of the fundamentally different mechanism of ferroelectricity in a 2D network, one can further challenge an uncharted mechanism of ferroelectricity in a 1D channel of M O x and estimate its feasibility. Here, ferroelectricity and coupled ferromagnetism in a 1D FeO4 tetrahedral chain network of a brownmillerite SrFeO2.5 epitaxial thin film are presented. The result provides a new paradigm for designing low‐dimensional M O x networks, which is expected to benefit the realization of macroscopic ferro‐ordering materials including ferroelectric ferromagnets. Abstract : A new class of room‐temperature ferroelectric ferromagnet in a 1D tetrahedral network is presented. Compared to the conventional ferroelectrics of 3D and 2D polyhedral networks, 1D tetrahedral networks exhibit an uncharted physical mechanism, which is the combined polar distortion for ferro‐orderings. Engineering polyhedral networks in 1D unveils novel pathways to design and realize functionalities in transition‐metal oxides.